The Scientific Study of Personal Wisdom From Contemplative Traditions to Neuroscience - Ferrari, Michel; Weststrate, Nic M.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
The rich and diverse contributions to this volume span a wide variety of disciplines, from psychology and philosophy to neuroscience, by some of the most influential scholars in the emerging science of personal wisdom. As such, it is a collection of essential readings and the first publication to integrate both the spiritual and pragmatic dimensions of personal wisdom. The content of the book goes beyond speculative theory to present a wealth of scientific research currently under way in this expanding field. It also describes numerous promising methods now being deployed in the quest for scientific knowledge of the elusive, yet critical, phenomenon of personal wisdom. The book is an excellent introduction to the field for novice researchers as well as a stimulating and enlightening resource for established experts. Its broad appeal makes it a vital addition to the libraries of academics and practitioners in many disciplines, from developmental psychology to gerontology, and from philosophy to contemplative religious traditions such as Buddhism.
Preface, Michel Ferrari & Nic M. Weststrate -- Part I: Person-based Wisdom -- Chapter 1. The Need to Distinguish Personal from General Wisdom: A Short History and Empirical Evidence, Ursula M. Staudinger -- Chapter 2. Relevance, Meaning and the Cognitive Science of Wisdom, John Vervaeke & Leo Ferraro -- Chapter 3. Personal Wisdom in the Balance, Robert J. Sternberg -- Chapter 4. The MORE Life Experience Model: A Theory of the Development of Wisdom, Judith Glück & Susan Bluck -- Chapter 5. Neurobiological Basis of Personal Wisdom, Jeff D. Sanders & Dilip V. Jeste -- Part II: Wisdom in everyday, real-life contexts -- Chapter 6. From Persons to Positive Influences: Exploring Wisdom in Real-life Contexts, Shih-ying Yang -- Chapter 7. Stories of Wisdom to Live By: Developing Wisdom in a Narrative Mode, Michel Ferrari, Nic M. Weststrate, & Anda Petro -- Chapter 8. Religion, Spirituality, and Personal Wisdom: A Tale of Two Types, Paul Wink & Michele Dillon -- Chapter 9. Social Interpretation of Wisdom, Ricca Edmondson -- Part III: Self-transcendent wisdom -- Chapter 10. The Transpersonal in Personal Wisdom, Michael R. Levenson & Carolyn M. Aldwin -- Chapter 11. The Grinch Who Stole Wisdom, Eleanor Rosch -- Chapter 12. Wisdom of the East and West: A Relational Developmental Systems Perspective, Masami Takahashi -- Chapter 13. The Paradoxical Nature of Personal Wisdom and its Relationship to Human Development in the Cognitive, Reflective and Affective Domains, Monika Ardelt, W. Andrew Achenbaum & Hunhui Oh -- Part IV: The transformative potential of wisdom inquiry -- Chapter 14. Wisdom: Object of Study or Basic Aim of Inquiry?, Nicholas Maxwell -- Conclusion, Michel Ferrari & Nic M. Weststrate.
Keywords: Education; Philosophy and social sciences; Education -- Philosophy; Educational psychology; Education -- Psychology; Education; Educational Psychology; Philosophy of Education; Educational Philosophy; Electronic books